Symposium 3: Collaborative Curiosity: Demonstrating relationships between open education, networked learning and connected learning - Gogia, Laura (Proceedings of the International Conference on Networked Learning, 2016)
Networked learning, open education, and connected learning are emerging pedagogical fields that explore the opportunities, challenges, and implications of teaching and learning in digital environments. Propelled forward from and by a digital networked participatory culture, the three pedagogical approaches share core assumptions about the importance of educational equality and access, self-determined and participatory learning, and authentic and relevant learning experiences. While open education, networked learning, and connected learning share an ethical stance, they emphasize different aspects of the digital pedagogical experience and manifest themselves in different ways. While the open education field tends to focus on the development and scalability of educational resources and practices, networked learning tends to emphasize the pedagogical experience of learning communities and interpersonal connections, and connected learning promotes instructional designs for holistic, participatory learning. Moreover, the scholarly outlets that support research and development across open education, networked learning, and connected learning exist in distinct educational sectors and geographic locations; in recent years, open education has evolved on a global scale, but networked learning is most commonly associated with universities in the United Kingdom and Europe, and connected learning is experiencing growth in the informal, K-12 learning spaces of the United States. After providing a brief historical and epistemological introduction to open education, networked learning, and connected learning, this paper aims to explore the relationships between them by analysing their intertwined presence within a single university course. The course, Collaborative Curiosity: Designing Community-Based Research (CMST 691), was a fully online, open, graduate-level course offered by Virginia Commonwealth University (VCU) in the summer of 2015. As part of a university-wide initiative to promote student engagement and deeper learning through digital engagement and connected learning, the course was intentionally designed to align with open education, networked learning, and connected learning practices. After teasing out and discussing the elements of “open,” “networked,” and “connected” as separate entities, this paper will briefly argue for treating them as distinct but related and synergistic educational approaches. Attempts should be made to build a common language and maintain pathways for communication across open education, networked learning, and connected learning scholars and scholarship, so that they will not become isolated by their existence in separate geographies.